The evolution of aluminum accumulation in ferns and lycophytes. Issue 4 (20th April 2017) - Schmitt, Marco; Mehltreter, Klaus; Sundue, Michael; Testo, Weston; Watanabe, Toshihiro; Jansen, Steven
Abstract : PREMISE OF THE STUDY: This paper investigates the occurrence and evolution of aluminum (Al) accumulation within ferns and lycophytes, which is characterized by Al concentrations above 1000 mg·kg −1 in aboveground plant tissues. We hypothesize that this feature is more common in ferns than in angiosperms, and potentially correlated with growth form and other chemical elements. METHODS: Aluminum concentrations were obtained from novel analyses and literature for a total of 354 specimens and 307 species. Moreover, a semiquantitative aluminon test was applied for a subset of 105 species and validated against exact Al measurements. KEY RESULTS: Molecular phylogenetic analyses showed that the major Al‐accumulating groups were primarily found in the Gleicheniales and Cyatheales, and largely absent in the Polypodiales. At the species and generic level, Al accumulation was typically either absent or present, and mixed results within a single species and genus were limited to less than 30% of the species and genera tested. Epiphytic ferns had significantly lower Al levels than terrestrial ferns, although this finding was not significant after phylogenetic correction. In addition, a significant, positive correlation was found between Al and iron, while Al was negatively correlated with phosphorus and potassium concentrations. CONCLUSIONS: Aluminum accumulation is most common outside of the Polypodiales and occurs in 38% of the species studied, indicating that this trait is indeed common within subtropical and tropical ferns, a finding that could be in line with their role as pioneer species on landslides and soils with high levels of soluble Al.